A randomized trial on the effects of root resorption after orthodontic treatment using pulsating force - Jue Wang; Ejvis Lamani; Terpsithea Christou; Peng Li; Chung How Kau (BMC Oral Health, 2020)
Abstract Background An orthodontic device that moves teeth with pulsating force was invented and underwent a single center, controlled, clinical trial to test its safety and efficacy for treatment. The device has a custom-made thermo-plastic mouthpiece which fits over the teeth with an inflatable silicone element. A console that measures and controls the pulsating force level in real-time controls the air pressure that delivers a pulsating force. In this study, the effect of the device on root resorption during orthodontic treatment was evaluated using 3D cone beam computed tomography and compared with a control group of patients who received Invisalign treatment. Methods Twenty-eight subjects were enrolled in the investigational arm and 15 in the control group. Subjects were followed until the average score of the mandibular and maxillary teeth achieved a Little’s Irregularity Index of 1.5 mm or less. Results There were no adverse events reported throughout the study for either treatment arm. No clinically significant root resorption was observed for either group. The investigational device did not cause root resorption greater than the control group. Both devices produced a safety profile compared to current orthodontic techniques. Conclusion The investigational device did not produce more root resorption than similar conventional orthodontic appliances. Trial registration ClinicalTrials.gov, NCT03421886 . Registered 12 January 2018 - Retrospectively registered.